Locked In Syndrome, a Rare Clinical Presentation: A Case Report - Bhattarai, Nischal; Tamrakar Karki, Karuna; Thapa, Dinesh Kumar (Eastern Green Neurosurgery, 2022)
Locked in syndrome is a rare neurological entity which is usually misdiagnosed as a spinal pathology. Here we report 70 years-old hypertensive and diabetic gentleman presented with quadriplegia without upsetting his conscious level.